Investigation of answer changes on the USMLE® Step 2 Clinical Knowledge examination - Ouyang, Wenli (BMC Med Educ, 2019)
BACKGROUND: Examinees often believe that changing answers will lower their scores; however, empirical studies suggest that allowing examinees to change responses may improve their performance in classroom assessments. To date, no studies have been able to examine answer changes during large scale professional credentialing or licensing examinations. METHODS: In this study, we expand the research on answer changes by analyzing responses from 27,830 examinees who completed the Step 2 Clinical Knowledge (CK) examination between August of 2015 and August of 2016. RESULTS: The results showed that although 68% of examinees changed at least one item, the overall average number of changes was small. Among the examinees who changed answers, approximately 45% increased their scores and approximately 28% decreased their scores. On average, examinees spent shortest time on the item changes from wrong to right and they were more likely to change their scores from wrong to right than right to wrong. CONCLUSIONS: Consistent with previous studies, these findings support the beneficial effects of answer changes in high-stakes medical examinations and suggest that examinees who are overly cautious about changing answers may put themselves at a disadvantage.